Projection of shadow price of beef cattle in the Bali beef fattening industry - Sintya J.K Umboh; Sasongko Wijoseno Rusdianto; Erwin Wantasen (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Any changes in supply and demand result in the imperfect development of a market mechanism, so a disequilibrium price occurs. Price changes, sometimes, do not reflect the prevailing price, issued by an agricultural business. Therefore, this research aims to project the shadow price of beef cattle (output) in the Bali beef fattening industry, utilizing cost production theory. Technically, the comparison of the total of the shadow prices of beef cattle employed two methods, such as a total of revenue and total cost. The research was conducted in the Regency of Lombok Tengah from July to September 2020. Then, the site and group of farmers were determined by purposive sampling. The criteria of samples were farmers performing the Bali beef fattening industry with an intensive raising system, utilizing cross-section data collected via interview and questionnaire. In conclusion, it is found that the shadow price of beef cattle was higher than the market price. It caused non-responsive market price changes unless a great change occurred. The shadow price was established by a greater marginal cost than marginal revenue.